Penilaian Kawasan Hutan dalam Penentuan Kelayakan Luas Areal Perkebunan Kelapa Sawit (Suatu Pendekatan Konseptual) - Yani, Akhmad (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2015)
Most   studies valuation that have been described previously including forest ecosystems do not see the forest ecosystem services as natual capital / natural assets and even the socio-ecological context. The implication is that forest ecosystem services are considered as an economic asset / economic capital.   the concept of value used in the valuation is the concept of the value of output.  Though the forest ecosystem services has the characteristics of a sustainable dynamic and as part of the life supporting system including the ability resilience and self-terrific capacity. So that the forest ecosystem is no longer seen as economic assets, but with the characteristics of the dynamic and sustainable forest ecosystem is seen as natural or natural capital assets. The current perspective marginalize other forest ecosystem functions, such as socio-economic functions. Whereas the concept of an insurance value of forest ecosystems is not just the case as seen from the perspective as natural capital, but the role of social values in maintaining the sustainability of forest ecosystems is crucial, as reflected by the presence of heritage value, and existence value. So that the insurance value of the forest ecosystem occurs because the forest ecosystem serves as a natural asset / natural and social capital assets / social capital.